Durabilidade de madeiras do gênero Eucalyptus termorretificadas em óleo vegetal - Andrade, Fernanda Regina (2019)
The present research had the objective of verifying the efficiency of the thermorectificated in vegetal oil in the improvement of the durability of the wood of Eucalyptus cloeziana and Eucaliptus grandis submitted to biodegradation in field test. To achieve this, five trees of each species were randomly selected to prepare the samples. The thermorectificated was performed in a laboratory oil bath at 130 ° C, 160 ° C, 190 ° C and 220 ° C for 2 and 4 hours. The field test was installed at the Federal University of Santa Maria, in the municipality of Santa Maria - RS. For the evaluation, samples were collected every three months in the 12-month period, totaling four samples, after each collection, the test specimens were arranged in an air-conditioned room until the mass stabilization. Then, we evaluated the deterioration index, weight loss and mechanical properties (static bending), physical properties (TUeq and WRE%) and superficial (wettability and colorimetry) tests of the Eucalyptus wood. The statistical analysis was performed in a 9x5 factorial arrangement, with nine levels for the thermal treatment factor and five levels for rotting field evaluations (collections) and Kruskal Wallis test when the data did not reach the normality and homogeneity of variance assumptions. The main results show that for the behavior index and weight loss the heat treatments were more satisfactory in relation to the control treatment, indicating a higher resistance to the treated wood. The mechanical properties were slightly altered in the thermal treatment and suffered smaller variations over the time of field exposure when compared to in natura wood. The physical properties were increased with thermal treatment and were generally more stable during the exposure time. The coloring of the wood was altered both by heat treatment and by the time of field exposure. The increase in temperature made the wood darker and decreased the color variation during the 360 days in the field. The wettability increased with the heat treatment, but remained more stable during the exposure period if it was lower at the end of 360 days in the treated woods. Therefore, the heat treatment in oil has more markedly altered the technological properties of the studied wood and was efficient in its maintenance during the period in rotting field. Therefore, it is recommended to use heat-treated wood in oil (preferably with a temperature of 190 ° C and 220 ° C) in outdoor environments and in contact with the soil.